Identification of human chromosome 22 transcribed sequences with ORF expressed sequence tags - de Souza, S. J.; Camargo, A. A.; Briones, MRS; Costa, F. F.; Nagai, M. A.; Verjovski-Almeida, S.; Zago, M. A.; Andrade, LEC; Carrer, H.; El-Dorry, HFA; Espreafico, E. M.; Habr-Gama, A.; et al. (Natl Acad Sciences, 2000)
Transcribed sequences in the human genome can be identified with confidence only by alignment with sequences derived from cDNAs synthesized from naturally occurring mRNAs. We constructed a set of 250,000 cDNAs that represent partial expressed gene sequences and that are biased toward the central coding regions of the resulting transcripts. They are termed ORF expressed sequence tags (ORESTES). The 250,000 ORESTEs were assembled into 81,429 contigs. of these, 1,181 (1.45%) were found to match sequences in chromosome 22 with at least one ORESTES contig for 162 (65.6%) of the 247 known genes, for 67 (44.6%) of the 150 related genes, and for 45 of the 148 (30.4%) EST-predicted genes on this chromosome. Using a set of stringent criteria to validate our sequences, we identified a further 219 previously unannotated transcribed sequences on chromosome 22. of these, 171 were in fact also defined by EST or full length cDNA sequences available in GenBank but not utilized in the initial annotation of the first human chromosome sequence. Thus despite representing less than 15% of all expressed human sequences in the public databases at the time of the present analysis, ORESTEs sequences defined 48 transcribed sequences on chromosome 22 not defined by other sequences. All of the transcribed sequences defined by ORESTEs coincided with DNA regions predicted as encoding exons by GENSCAN.